High-throughput transformation pipeline for a Brazilian japonica rice with bar gene selection - Dedicova, Beata; Bermudez, C.; Prias, Monica A.; Zuñiga, E; Brondani, C. (Springer, 2015)
The goal of this work was to establish a transformation pipeline for upland Curinga rice (Oryza sativa L. ssp. japonica) with bar gene selection employing bialaphos and phosphinothricin as selection agents. The following genes of interest: AtNCED3, Lsi1, GLU2, LEW2, PLD-alpha, DA1, TOR, AVP1, and Rubisco were cloned into the binary vector p7i2x-Ubi and were transferred into Agrobacterium strain EHA 105. Embryogenic calli derived from the mature embryos were transformed, and transgenic cells and shoots were selected on the medium supplemented with bialaphos or phosphinothricin (PPT) using a stepwise selection scheme. Molecular analyses were established using polymerase chain reaction and Southern blot for the bar gene and the NOS terminator. Overall, 273 putative transgenic plants were analyzed by Southern blot with 134 events identified. In total, 77 events had a single copy of the transgene integrated in the plant genome while 29 events had two copies. We tested backbone integration in 101 transgenic plants from all constructs and found 60 transgenic plants having no additional sequence integrated in the plant genome. The bar gene activity was evaluated by the chlorophenol red test and the leaf painting test using phosphinothricin with several transgenic plants. The majority of T0 plants carrying the single copy of transgene produced T1 seeds in the screen house.